To determine which equation can replace \(3x + 5y = 59\) in the original system while still producing the same solution, we will first solve the original system of equations.
The given equations are:
- \(2x - y = -4\)
- \(3x + 5y = 59\)
Step 1: Solve for \(y\) from the first equation
From \(2x - y = -4\):
\[ y = 2x + 4 \]
Step 2: Substitute \(y\) into the second equation
Substituting \(y\) into \(3x + 5y = 59\):
\[ 3x + 5(2x + 4) = 59 \] \[ 3x + 10x + 20 = 59 \] \[ 13x + 20 = 59 \] Subtracting 20 from both sides: \[ 13x = 39 \]
Step 3: Determine the replacement equation
We see that \(13x = 39\) is derived from the original system. Thus, \(13x = 39\) can replace \(3x + 5y = 59\) in the original system while still producing the same solution.
Conclusion
The equation that can replace \(3x + 5y = 59\) is:
\[ 13x = 39 \]
This is the correct answer.